2017
DOI: 10.1001/jamaoncol.2016.3904
|View full text |Cite|
|
Sign up to set email alerts
|

Vaginal Testosterone Cream vs Estradiol Vaginal Ring for Vaginal Dryness or Decreased Libido in Women Receiving Aromatase Inhibitors for Early-Stage Breast Cancer

Abstract: clinicaltrials.gov Identifier: NCT00698035.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 30 publications
0
102
0
3
Order By: Relevance
“…Patients who wish to consider HT after a diagnosis of breast cancer should be informed that definitive evidence on its influence in prognosis of breast cancer is lacking. The results of observational studies (which are fraught with potential biases) [Biglia et al 2010;Manson et al 2014;Santen et al 2002;Cold et al 2015] and a recent phase II RCT (evaluating use of estradiol-releasing vaginal ring 7.5 µg/d for 12 weeks) have been reassuring with respect to safety [Melisko et al 2016]. However, a single RCT suggested that HT in breast cancer survivors may increase breast cancer recurrence or new breast cancers by 2-3-fold [Holmberg and Anderson, 2004].…”
Section: Hormone Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who wish to consider HT after a diagnosis of breast cancer should be informed that definitive evidence on its influence in prognosis of breast cancer is lacking. The results of observational studies (which are fraught with potential biases) [Biglia et al 2010;Manson et al 2014;Santen et al 2002;Cold et al 2015] and a recent phase II RCT (evaluating use of estradiol-releasing vaginal ring 7.5 µg/d for 12 weeks) have been reassuring with respect to safety [Melisko et al 2016]. However, a single RCT suggested that HT in breast cancer survivors may increase breast cancer recurrence or new breast cancers by 2-3-fold [Holmberg and Anderson, 2004].…”
Section: Hormone Therapymentioning
confidence: 99%
“…Furthermore, vaginal administration of testosterone has been evaluated for the treatment of symptomatic genitourinary atrophy in postmenopausal women with breast cancer [Derzko et al 2007;Witherby et al 2011;Melisko et al 2016]. Witherby and colleagues reported results of a phase I/II pilot study on the effect of intravaginal testosterone (cream containing either 150 μg or 300 μg of testosterone) in breast cancer patients taking AIs [Witherby et al 2011].…”
Section: Androgensmentioning
confidence: 99%
See 1 more Smart Citation
“…101,123127 A study of 76 postmenopausal breast cancer survivors on aromatase inhibitor therapy found that intravaginal testosterone cream or an estradiol-releasing vaginal ring were safe and improved vaginal atrophy and sexual function. 211 …”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…74 However, recent evidence from a randomised controlled trial assessing the efficacy and systemic absorption of vaginal oestrogen (via a ring) in 69 breast cancer survivors taking aromatase inhibitors demonstrated improvements in vaginal dryness and sexual function with no increase in systemic oestradiol at 12 weeks compared with baseline, suggesting that vaginal oestrogen may be safe to use in breast cancer survivors. 75 Current guidelines from the American College of Obstetrics and Gynaecology recommend reserving vaginal oestrogens for intransigent vaginal dryness in breast cancer survivors, discussion with the treating oncologist, and inclusion of the patient in decision making when considering potential risks and benefits. 76 Ospemifene is a selective oestrogen receptor modulator that is superior to placebo for vaginal dryness.…”
Section: Topical Treatments For Vaginal Symptoms Of Menopause Topicalmentioning
confidence: 99%